2015
DOI: 10.1007/s00259-015-3051-4
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of standardized uptake value and metabolic tumour volume on 18F-FDG PET/CT in oropharyngeal squamous cell carcinoma

Abstract: SUVmax and MTV measured on pretreatment (18)F-FDG PET/CT may be useful in predicting the clinical outcomes in OPSCC patients. This study investigated the clinical prognostic value of imaging parameters from pretreatment (18)F-FDG PET/CT in 221 patients who underwent definitive treatment for oropharyngeal squamous cell carcinoma. High maximum standardized uptake value and metabolic tumour volume were independently associated with decreased disease-free and overall survival outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
44
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(49 citation statements)
references
References 34 publications
(63 reference statements)
4
44
0
1
Order By: Relevance
“…The cut-off values for MTV predicting worse prognosis ranged between 7.7 and 45 cm3 and those of TLG ranged from 55 to 330 g 9 .. In a retrospective study including 221 patients, Kim et al 51 assessed the prognostic values of pre-treatment FDG-PET markers, as SUV max , MTV, and TLG in a uniform sample of only OPSCC patients, although the HPV status was obtained for a limited sample of patients. Using univariate Cox proportional hazards regression analysis, investigators concluded that age > 60 years, advanced tumour stage, primary tumor SUV max > 7.55, SUV peak > 6.80, MTV > 11.06 ml, and TLG > 78.56 g. were significantly associated with decreased OS and disease-free survival.…”
Section: Discussionmentioning
confidence: 99%
“…The cut-off values for MTV predicting worse prognosis ranged between 7.7 and 45 cm3 and those of TLG ranged from 55 to 330 g 9 .. In a retrospective study including 221 patients, Kim et al 51 assessed the prognostic values of pre-treatment FDG-PET markers, as SUV max , MTV, and TLG in a uniform sample of only OPSCC patients, although the HPV status was obtained for a limited sample of patients. Using univariate Cox proportional hazards regression analysis, investigators concluded that age > 60 years, advanced tumour stage, primary tumor SUV max > 7.55, SUV peak > 6.80, MTV > 11.06 ml, and TLG > 78.56 g. were significantly associated with decreased OS and disease-free survival.…”
Section: Discussionmentioning
confidence: 99%
“…En accord avec les données de la littérature [28][29][30], nous avons alors observé que le volume métabolique tumoral initial apparaît comme un facteur pronostique, puisqu'il était significativement plus important ( p = 0,0005) dans le groupe de patients ayant récidivé localement, comparativement aux patients en rémission. Cette information pourrait permettre dans un premier temps de sélectionner initialement les patients ayant un MTV élevé, les plus à risques de récidive, qui pourraient bénéficier d'un traitement plus agressif.…”
Section: Discussionunclassified
“…A nuclear medicine physicist (Jungsu S. Oh) generated quantitative 18 F‐FDG activity measurements of tumors with PET data reconstruction and SUV equalization, and subsequently fed the reconstructed 18 F‐FDG PET data into an in‐house PET image quantification software program (AMC NM Toolkit for Image Quantification of Excellence; ANTIQUE) . 18 F‐FDG‐PET activity was determined by calculating SUV using decay‐corrected activity in the tissue divided by the injected dose of 18 F‐FDG per lean body mass of the patient.…”
Section: Methodsmentioning
confidence: 99%
“…18 F‐FDG PET/CT is used to assess the initial stages of disease and treatment responses, and to make posttreatment selections and prognostic predictions . The standardized uptake value (SUV) is a semiquantitative measurement of the tissue glucose metabolic rate, and a high value in a tumor may be associated with poor survival outcome . Moreover, volumetric PET parameters such as metabolic tumor volume (MTV) and total lesion glycolysis (TLG) have been recognized as potentially better predictors of treatment and survival .…”
Section: Introductionmentioning
confidence: 99%